Suppressor of Gamma Response 1 Modulates the DNA Damage Response and Oxidative Stress Response in Leaves of Cadmium-Exposed Arabidopsis thaliana - Hendrix, Sophie; Iven, Verena; Eekhout, Thomas; Huybrechts, Michiel; Pecqueur, Ingeborg; Horemans, Nele; Keunen, Els; De Veylder, Lieven; Vangronsveld, Jaco; Cuypers, Ann (Frontiers in Plant Science, 2020)
Cadmium (Cd) exposure causes an oxidative challenge and inhibits cell cycle progression, ultimately impacting plant growth. Stress-induced effects on the cell cycle are often a consequence of activation of the DNA damage response (DDR). The main aim of this study was to investigate the role of the transcription factor SUPPRESSOR OF GAMMA RESPONSE 1 (SOG1) and three downstream cyclin-dependent kinase inhibitors of the SIAMESE-RELATED (SMR) family in the Cd-induced DDR and oxidative challenge in leaves of Arabidopsis thaliana. Effects of Cd on plant growth, cell cycle regulation and the expression of DDR genes were highly similar between the wildtype and smr4/5/7 mutant. In contrast, sog1-7 mutant leaves displayed a much lower Cd sensitivity within the experimental time-frame and significantly smaller upregulations of DDR-related genes, indicating the involvement of SOG1 in the Cd-induced DDR. Cadmium-induced responses related to the oxidative challenge were disturbed in the sog1-7 mutant, as indicated by delayed Cd-induced increases of hydrogen peroxide and glutathione concentrations and smaller upregulations of oxidative stress-related genes. In conclusion, our results attribute a novel role to SOG1 in regulating the oxidative stress response and connect oxidative stress to the DDR in Cd-exposed plants.